ISOLASI DAN IDENTIFIKASI SENYAWA ALKALOID BUAH MAHKOTA DEWA (Phaleria macrocarpa (Scheff.) Boerl) SECARA SPEKTROFOTOMETRI UV-Vis DAN IR SERTA UJI TOKSISITAS AKUT TERHADAP LARVA Artemia salina Leach - Christina Astutiningsih; Frida Nuzulia; Agus Suprijono (Universitas Sanata Dharma, 2012)
Abstract: Fruit Mahkota Dewa (Phaleria macrocarpa (Scheff.) Boerl) contains alkaloid, tannin, saponin, flavonoid, terpenoid dan lignin. The aim of this study was to elucidate compound from Mahkota Dewa based on the analyses on spectrophotometry UV-Vis, IR and to evaluate the compound in the Brine Shrimp Lethality Test. On IR spectra revealed the presence of alkaloid amin primer. The isolated alkaloid compound was found to be toxic to brine shrimp with LC50 33.8932 μg/ml. Keywords: alkaloid, Mahkota Dewa, toxicity, Artemia salina Leach